CRISPRi-mediated suppression of E. coli Nissle 1917 virulence factors: A strategy for creating an engineered probiotic using csgD gene suppression - Azam, Mohd W.; Khan, Asad U. (Frontiers in Nutrition, 2022)
Background Biofilm formation is a complex phenomenon, and it is the causative agent of several human infections. Bacterial amyloids are involved in biofilm formation leading to infection persistence. Due to antibiotic resistance, their treatment is a great challenge for physicians. Probiotics, especially E. coli Nissle 1917 (EcN), are used to treat human intestinal disorders and ulcerative colitis. It also expresses virulence factors associated with biofilm and amyloid formation. EcN produces biofilm equivalent to the pathogenic UPEC strains and also produces genotoxin colibactin. Methods CRISPRi was used to create the knockdown mutants of the csgD gene (csgD-KD). The qRT-PCR was performed to assess the expression of the csgD gene in csgD-KD cells. The csgD-KD cells were also evaluated for the expression of csgA, csgB, fimA, fimH, ompR, luxS, and bolA genes. The gene expression data obtained was further confirmed by spectroscopic, microscopic, and other assays to validate our study. Results CRISPRi meditaed knockdown of csgD gene shows reduction in curli amyloid formation, biofilm formation and suppression of genes (csgA, csgB, fimA, fimH, ompR, bolA, and luxS) involved in virulence factors production. Conclusion Curli amyloid fibres and fimbriae fibres play a critical role in biofilm formation leading to pathogenicity. CsgD protein is the master regulator of curli synthesis in E. coli. Hence curli amyloid inhibition through the csgD gene may be used to improve the EcN and different probiotic strains by suppressing virulence factors.